Enhanced brain targeting of temozolomide in polysorbate-80 coated polybutylcyanoacrylate nanoparticles - Xin-Hua Tian (Dove Medical Press, 2011)
Xin-Hua Tian1, Xiao-Ning Lin1, Feng Wei1, Wei Feng1, Zhi-Chun Huang1, Peng Wang1, Lei Ren2, Yi Diao11Department of Neurosurgery, Zhongshan Hospital of Xiamen University, Xiamen, People's Republic of China; 2Research Center of Biomedical Engineering, Xiamen, People's Republic of ChinaBackground: Polybutylcyanoacrylate (PBCA) nanoparticles coated with polysorbate-80 have been extensively proposed for delivering drugs into the animal brain and have shown great potential for therapeutic applications. In this study, we made an attempt to deliver the chemotherapeutic drug, temozolomide, into the brain by using PBCA nanoparticles. The physicochemical characteristics, in vitro release, and brain targeting ability of the drug-loaded nanoparticles were investigated.Results: Our results show that a significantly higher concentration of temozolomide in the form of polysorbate-80-coated PBCA nanoparticles was observed in the brain (P < 0.05) in comparison with the free drug.Conclusion: This study indicates that polysorbate-80 coated PBCA nanoparticles could be a feasible carrier for temozolomide delivery to the brain. It is anticipated that the developed formulation may improve on targeted therapy for malignant brain tumors in the future.Keywords: temozolomide, polybutylcyanoacrylate, nanoparticles, polysorbate-80, brain targeting